The Impact of Teaching the Lives of Scientists in a Mobile Augmented Reality Environment on Students' Success and Opinions - Kececi, Gonca; Yildirim, Pelin (Taylor & Francis Inc, 2025)
This research aims to investigate the impact of a Mobile Augmented Reality (MAR) application called TISAR-3D on the success and opinions of secondary school students when learning about the lives of scientists. A mixed-method approach was employed. The research was conducted on students in the 7th grade of a public school located in the city center of Elazig, Turkey. The sample consisted of 90 students, comprising 41 girls and 49 boys. The research was conducted with one experimental and one control group. Over the course of eight weeks, the experimental group utilized the TISAR-3D application, while the control group acquired knowledge by reading texts about scientists. The research showed that students using the MAR application had significantly higher academic success than the control group. Interviews with the experimental group supported integrating MAR technology, indicating it improved understanding of science topics and boosted academic success. Teachers are recommended to use the TISAR-3D application in their lessons to enhance students' learning experiences.
Keywords: Mobile augmented reality; scientists; academic success; student opinions; secondary school students